Research on the Effectiveness of College Student English Writing Teaching Based on Data-Driven Learning - Mao, Lidan; Liu, Yang; Zhang, Mingjie (Educational sciences : theory & practice, 2018)
Data-driven learning is a kind of new teaching mode under which language library is applied to language teaching. Featured by discovery learning, diversified learning process, media learning materials and instructional learning style, it can better stimulate students’ learning initiatives, improve their self-learning ability and increase their learning efficiency. As the English writing level of college students is the most important indicator of students’ subjective initiative in learning and their own English proficiency, this paper applies data-driven learning (DDL) in college students’ English writing teaching in combination of the process writing approach. It selects 52 college students in a normal college in Hebei Province as the test subjects, and then through detailed experimental design and the pre-test, mid-test and post-test, discusses the effectiveness of data-driven learning in college English writing teaching. At last, through a questionnaire survey, this paper shows the students’ attitudes towards the new data-driven learning method. This paper provides certain theoretical guidance to the improvement of the English writing level of college students.